2013
DOI: 10.7567/jjap.53.01ab03
|View full text |Cite
|
Sign up to set email alerts
|

Partially fluorinated copper phthalocyanine toward band engineering for high-efficiency organic photovoltaics

Abstract: Thermoluminescence emission spectra of six phosphors commonly used for TL dosimetry are presented at doses between 15 mGy and 1 Gy. The use of a Fourier transform spectrometer has made it possible to obtain spectra at doses considerably lower than those for spectra previously reported. The spectra are in the form of isometric plots of intensity versus temperature and wavelength. They are compared with previous observations at higher doses with comments on the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…To model the organic-metal and organic-organic interfaces of figure 1, phthalocyanine-derivatives are chosen because they allow simple replacement of central atoms and further functionalization by molecular side groups [78,79]. We use titanyl-phthalocyanine (TiOPc) as the bottom layer of the heterostructure: the intrinsic dipole moments of TiOPc have an antiparallel orientation in the first and second layer on Ag(111) with layer-by-layer growth and thereby provide a stable, weakly interacting contact layer [80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…To model the organic-metal and organic-organic interfaces of figure 1, phthalocyanine-derivatives are chosen because they allow simple replacement of central atoms and further functionalization by molecular side groups [78,79]. We use titanyl-phthalocyanine (TiOPc) as the bottom layer of the heterostructure: the intrinsic dipole moments of TiOPc have an antiparallel orientation in the first and second layer on Ag(111) with layer-by-layer growth and thereby provide a stable, weakly interacting contact layer [80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…11,12) The fluorination of phthalocyanines leads to a decrease in energy level depending on the number of fluorine atoms. [13][14][15][16][17][18][19] It has been reported that organic transistors having hexadecafluoro CuPc (F 16 CuPc) as a channel material operate as n-channel transistors. 8,20) This indicates that F 16 CuPc works as an ntype semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…Most organic semiconductors, including the majority of thin Pc films, are p-type materials. Therefore, the publications demonstrating that copper phthalocyanine fluorination (formation C 32 H 12 N 8 CuF x (CuPcF x ), x = 4, 8, 16) causes the lowest unoccupied molecular orbital (LUMO) and the highest occupied molecular orbital (HOMO) to move in the direction of higher binding energies are particularly attractive. As a result, the position of the Fermi level in the band gap is shifted toward the LUMO bottom, which is a prerequisite for the change of the hole conductivity in copper phthalocyanine (CuPc) to the electron conductivity in CuPcF x . This means that CuPcF x is an exclusive material with a wide band gap and delocalized π orbitals for organic-based electronic devices .…”
Section: Introductionmentioning
confidence: 99%